2019
DOI: 10.1027/0227-5910/a000548
|View full text |Cite
|
Sign up to set email alerts
|

Family, Health, and Poverty Factors Impacting Suicide Attempts in Cambodian Women

Abstract: Abstract. Background: Our recent report demonstrates that 5.5% of Cambodian women have previously attempted suicide. Despite these high rates and critical need for intervention, research on suicide attempts in Cambodia is lacking, and life-saving information on suicide prevention is therefore unknown. Aims: This study explores factors impacting Cambodian women suicide attempts. Method: A total of 1,801 women participated in the large national survey during which 100 of these women (5.5%) reported at least one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…In Bangladesh, Li et al (2021) 26 found a 6.5% rate of SA among women, most (88.5%) occurring within one year after pregnancy. Similarly, Seponski et al (2019) 27 , in Cambodia, found a 5.5% prevalence of SA among women (n = 100).…”
Section: Discussionmentioning
confidence: 75%
“…In Bangladesh, Li et al (2021) 26 found a 6.5% rate of SA among women, most (88.5%) occurring within one year after pregnancy. Similarly, Seponski et al (2019) 27 , in Cambodia, found a 5.5% prevalence of SA among women (n = 100).…”
Section: Discussionmentioning
confidence: 75%
“…Em Bangladesh, Li et al (2021) 26 encontraram taxa de TS de 6,5% entre mulheres, com a maioria delas (88,5%) ocorrendo em até um ano após a gravidez. Similarmente, Seponski et al (2019) 27 , no Camboja, identificaram prevalência de TS em mulheres de 5,5% (n = 100).…”
Section: Discussionunclassified
“…Numerous studies have supported the notion that suicide is associated with an individual's financial status, but rather that association is positive or negative depends on both the population of interest and other factors at play [21][22][23]. These studies have spanned numerous nations across the globe but include considerably more Western countries [6,20,24,25].…”
Section: Psychologymentioning
confidence: 99%
“…These studies have spanned numerous nations across the globe but include considerably more Western countries [6,20,24,25]. Studies of survivors of suicide attempts in South Korea and Europe found financial stress to be one of the most commonly reported reasons for a suicide attempt for middle-aged individuals, while a similar study of female suicide attempt survivors in Cambodia found poverty to be one of four reasons reported for attempting suicide [22,26,27]. Quantitative analyses of suicide rates in Brazil, Germany, China, and other nations have concluded that economic deprivation is positively correlated with rates of death by suicide, while economic success is negatively correlated with rates of death by suicide [5,17,28,29].…”
Section: Psychologymentioning
confidence: 99%